Legal Consequences for Companies that Carry Out Unilateral Termination of Employment - I Gusti Ayu Putu Lingsiani Ayu; I Gede Agus Kurniawan (Borong Newinera Publisher, 2024)
The COVID-19 pandemic has resulted in the Company taking steps to streamline company costs by laying off workers. Many companies experience labor relations disputes, one of which is that the company carries out unilateral termination of employment (PHK) of workers without negotiating with the workers and does not pay attention to the rights of these workers. This research aims to find out and examine the mechanism for resolving industrial relations disputes in Badung Regency as well as knowing and studying the legal consequences for companies that carry out unilateral layoffs of workers with a fixed term work agreement (PKWT) and workers with a fixed term work agreement (PKWTT) in Badung Regency. This research is empirical legal research with a factual approach and a statutory approach. The research results confirm that there are 2 (two) alternative dispute resolution mechanisms for industrial disputes, either through non-litigation channels, namely by bipartite negotiations, mediation, conciliation, arbitration or by litigation, namely through the industrial relations court (PHI). Layoffs can be said to be valid if they have received a decision from the PHI and if without this decision the employer continues to lay off workers in PKWT and PKWTT who received layoffs unilaterally, then the layoffs are not legally valid and are considered null and void. The legal sanction for employers who lay off PKWT workers before their term of employment ends is to fulfill the workers' rights, namely by providing severance pay, gratuity money, compensation money due to the layoff.